Beyond fatalism: An empirical exploration of self-efficacy and aspirations failure in Ethiopia - Bernard, Tanguy; Dercon, Stefan; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2012)
Fatalism is considered pervasive, especially in many poor communities. In this paper, we explore whether fatalistic beliefs have implications for the attitudes and behavior of poor rural households toward investment in the future. To explore the idea of fatalism, we draw inspiration from theories in psychology focusing on the role of locus of control and self-efficacy and also from the theoretical framework of aspiration failure as developed in recent economic literature. Using survey data from rural Ethiopia, we find evidence of fatalistic beliefs among a substantial group of rural house-holds, as well as indicators consistent with narrow aspirations gap and low self-efficacy. We also find that such beliefs consistently correlate with lower demand for credit, in terms of loan size, repayment horizon, and productive purposes.